Effects of dam construction and increasing pollutants on the ecohydrological evolution of a shallow freshwater lake in the Yangtze floodplain - Zeng, Linghan; McGowan, Suzanne; Cao, Yanmin; Chen, Xu (Elsevier, 2018)
Large river-floodplain systems which provide a variety of societal, economic and biological benefits are undergoing extensive and intensive human disturbance. However, floodplain lakes responses to multiple stressors are poorly understood. The Yangtze River and its floodplain which provide water and food resources for more than 300 million people are an important region in China. Hydrological regulation as well as socio-economic development have brought profound negative influence on this ecologically important area. To improve understanding of decadal-scale responses of floodplain lakes to multiple stressors, lake sediment proxies including particle size, geochemical elements, diatoms and chironomids were analysed in a lead-210 dated core from Futou Lake. The analyses show that dams constructed in 1935 and the early 1970s stabilized hydrological conditions in Futou Lake and impeded the interaction with the Yangtze River, resulting in a decrease in major elements (e.g., Mg, Al, Fe) transported into the lake and an increase of macrophyte-related chironomids (C. sylvestris-type, P. penicillatus-type and Paratanytarsus sp.). After the late 1990s, further decreases in major elements and increases in median grain size are attributed to the erosion of the Yangtze riverbed and declining supply of major elements-enriched sediments from the upper Yangtze caused by the impoundment of the Three Gorges Dam. Chironomid and diatom assemblages indicate that hydrological stabilization caused by dam constructions stimulated the growth of macrophytes, which may be important in buffering against an ecosystem state change towards a phytoplankton-dominated and turbid state with ongoing eutrophication. However, a recent increase in Zn, TP and the emergence of eutrophic diatom and chironomid species indicate initial signs of water quality deterioration which may be related to the combined effects of hydrological stabilization and aquaculture. Over all, the sediment record from Futou Lake emphasizes the importance of interactions between hydrological change and pollutant loads in determining floodplain lake ecosystem state.